The Status of Normative Ethical Decision-Making Models: The Development and Application of an Analytical Framework - Versteegt, Jop; van Dijke, Marius; Kaptein, Muel (Journal of business ethics, 2025)
Normative ethical decision-making models (NEDMs) are designed to enhance ethical decision-making. NEDMs are widely employed in business contexts. Unfortunately, there is no overview of NEDMs available in the scholarly literature for use in business contexts. Additionally, there is no analytical framework that allows the classification, comparison, and evaluation of existing NEDMs. Our literature search identified 28 unique NEDMs published in the English-language scholarly business literature before May 2025. We subsequently developed a novel, four-dimensional NEDM analytical framework. Applying this framework to the identified models revealed that most NEDMs contain five to eight steps that must be followed in a fixed sequence, omit key decision-making steps, treat decision-makers as objective, primarily engage with classical ethical theories while making minimal attempts to weigh conflicting moral norms, values or principles, and prescribe how decisions should be made rather than prescribing decision outcomes. The majority of NEDMs also show no indication of being specific to the business context. In the Discussion section, we explain how the NEDM analytical framework uncovers important variations and limitations in existing business-oriented NEDMs, and how it can guide scholars in justifying, evaluating, and empirically testing new models—thereby advancing the field of business ethics both in theory and in practice.